An Analysis of Planning, Implementation, and Evaluation of TPACK-Based Chemistry Instruction in Grade X at SMAN 5 Mataram - Nasywa Dwi Kamila; Mahrus Mahrus; Fathoni Arif Pratama; Imam Arbi Arrahman; Muliana Lutfiatussholihah (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
Technology integration in 21st-century learning is essential to enhance the quality of chemistry education, which is often perceived as abstract and complex. This study aims to analyze the planning, implementation, and evaluation of TPACK-based chemistry learning in Grade X at SMAN 5 Mataram. This research employed a descriptive qualitative approach using a case study design, with data collected through observation, interviews, and documentation. The results show that teachers have integrated technology across all stages of learning through PowerPoint, instructional videos, Google Classroom, and Quizizz. However, the use of technology remains predominantly as a tool for content delivery rather than as a means to facilitate higher-order thinking skills. It indicates that the implementation of TPACK has not yet reached a transformative level of learning. In conclusion, although TPACK has been implemented across the planning, implementation, and evaluation stages, its effectiveness in supporting instructional processes remains limited. This study underscores the need to strengthen teachers’ competencies in designing technology-integrated learning that promotes critical and meaningful learning experiences. Practically, these findings can guide chemistry teachers in optimizing the use of digital tools to support more interactive and student-centered learning